Exotic and Primitive Lapland: Othering in ‘The Earth Is a Sinful Song’ (1973) - Hiltunen, Kaisa (Nordlit, 2019)
This article contributes to postcolonial cultural criticism by analyzing how since the 1920s, Lapland and its residents have been portrayed as exotic Others in Finnish feature films that are set in Lapland. The roots of the othering of Lapland go back to the nationalist aspirations of the Finns. The geographical distance of the northern region has bred mental distance, because of which Lapland has remained a source of exoticism for filmmakers, who almost invariably come from the South. Lapland can be seen as Finland’s spatial and cultural Other, an “internal Other” (Jansson 2003). This article asks what kind of strategies of othering are used in Rauni Mollberg’s film The Earth Is a Sinful Song (1973), which is the extreme example of othering among films that are set in Lapland. The film is based on Timo K. Mukka’s novel of the same name and it caused a sensation to contemporary audiences because of its harsh and naturalistic way of depicting life in a poor northern village in the late 1940s. The article analyzes the cinematic techniques and style that are used to represent the characters as primitive, over-sexed and uncivilized. It also places The Earth Is a Sinful Song in a continuum of ‘Lapland films’, showing that othering has taken many forms both before and after it.